PRIORITY DIRECTIONS AND PROSPECTS FOR ENSURING THE STABILITY OF THE STATE BUDGET - Aliyev Ma’ruf Komiljon O’g’li (American Journals, 2023)
The article identifies the concepts of budget stability and its main indicators and assesses the stability of the budget system. Debt stability is based on the fact that contraception provides conditions for fiscal policy - viewed as an important yelement of fiscal stability and that fiscal stability does not eat into the amount of debt, but depends on institutions of the budget system and public administration in general.
Keywords: state budget, stability, priority directions, budget system.